Showcasing the diversity of service research: Theories, methods, and success of service articles - BENOIT, Sabine (Institutional Knowledge at Singapore Management University, 2017)
Purpose: The purpose of this paper is to make two main contributions: first, showcase the diversity of service research in terms of the variety of used theories and methods, and second, explain (post-publication) success of articles operationalized as interest in an article (downloads), usage (citations), and awards (best paper nomination). From there, three sub-contributions are derived: stimulate a dialogue about existing norms and practices in the service field, enable and encourage openness amongst service scholars, and motivate scholars to join the field. Design/methodology/approach: A mixed method approach is used in combining quantitative and qualitative research methods while analyzing 158 Journal of Service Management (JOSM) articles on several criteria such as their theory, methodology, and main descriptive elements (e.g. number of authors or references) and then using automated text analysis (e.g. investigating the readability of articles, etc.). Findings: The results show that the JOSM publishes a large variety of articles with regard to theories, methods of data collection, and types of data analysis. For example, JOSM has published a mixture of qualitative and quantitative articles and papers containing firm-level and customer-level data. Further, the results show that even though conceptual articles create the same amount of interest (downloads), they are used more (citations). Research limitations/implications: This paper presents many descriptive results which do not allow for making inferences toward the entire service research discipline. Further, it is only based on one service research journal (JOSM) through a five-year span of publication. Practical implications: The results have a number of implications for the discipline that are presented and discussed. Amongst them are that: the discipline should be more open toward conceptual articles, service research shows an imbalance toward theory testing, there is more potential to work with transactional data, and writing style should be more accessible (i.e. readable). Originality/value: This paper is the first to conduct an in-depth analysis of service research articles to stimulate dialogue about common publishing practices in the JOSM and to increase the openness of the field.